Optimizing community-based management of hypertension and diabetes mellitus through the SEHATI book innovation: Optimalisasi pengelolaan hipertensi dan diabetes melitus berbasis komunitas melalui buku SEHATI - Sutriani Undariningsih; Evan Wahyuningsih; Dodi Wijaya; Rondhianto (KHD Production, 2026)
Non-communicable diseases (NCDs), particularly hypertension and diabetes mellitus, remain major contributors to morbidity and mortality in Indonesia. Suboptimal patient engagement and poor adherence to therapy continue to hinder effective NCD management at the primary care level. This community-based intervention aimed to enhance patients’ knowledge, treatment adherence, and self-management through the use of a print-based educational tool, the SEHATI book. The program was implemented over a one-week period at Tanjung Karang Primary Health Center, Mataram City, involving 17 participants, including healthcare providers, community health cadres, and patients with hypertension and diabetes. The intervention consisted of group education sessions, simulation activities, cadre-led home visits, and pre- and post-intervention assessments. The results demonstrated a substantial improvement in participants’ knowledge, increasing from 52% to 89%, and medication adherence, rising from 61% to 90%. Qualitative findings indicated that the SEHATI book facilitated self-monitoring practices and enhanced patient motivation. Additionally, health cadres reported that the tool strengthened their capacity as community educators. This community-based approach, particularly through the active involvement of health cadres, proved effective in promoting patient engagement, especially in settings with limited access to digital health resources. The intervention is consistent with the Health Belief Model, as it enhances perceived benefits and self-efficacy among patients. Overall, the SEHATI book represents a practical, scalable, and contextually appropriate educational strategy for sustainable NCD management in primary healthcare settings.